2021
DOI: 10.1093/cvr/cvab204
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of myocardial cathepsin-L release during reperfusion following myocardial infarction improves cardiac function and reduces infarct size

Abstract: Aims Identifying novel mediators of lethal myocardial reperfusion injury that can be targeted during primary percutaneous coronary intervention (PPCI) is key to limiting the progression of patients with ST-elevated myocardial infarction (STEMI) to heart failure. Here we show through parallel clinical and integrative preclinical studies the significance of the protease cathepsin-L on cardiac function during reperfusion injury. Methods and Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Here, we utilized a small molecule inhibitor (Ro5-3335) as a means of antagonizing RUNX1 and examined its effects on infarct size in the context of acute MI. Adult male Wistar rats were subjected to thoracotomy and left anterior descending coronary artery ligation through approaches we previously established (McCarroll et al 2018 ; He et al 2022 ). Ro5-3335 was administered immediately following coronary artery ligation by intraperitoneal injection at a dose of 10 mg/kg based on the previous study defining its effects on cardiac contractile function post-MI (Martin et al 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we utilized a small molecule inhibitor (Ro5-3335) as a means of antagonizing RUNX1 and examined its effects on infarct size in the context of acute MI. Adult male Wistar rats were subjected to thoracotomy and left anterior descending coronary artery ligation through approaches we previously established (McCarroll et al 2018 ; He et al 2022 ). Ro5-3335 was administered immediately following coronary artery ligation by intraperitoneal injection at a dose of 10 mg/kg based on the previous study defining its effects on cardiac contractile function post-MI (Martin et al 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study has shown that programmed cell death pathways can be therapeutically targeted to limit infarct size. He et al (He et al 2022 ) demonstrated activated apoptosis in cardiomyocytes obtained from ex vivo isolated rat hearts which are subjected to ischemia followed by reperfusion. Pharmacological treatment antagonizing cathepsin-L in ex vivo hearts showed effects of suppressing apoptosis and reducing infarct size (He et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The circulating and tissue levels of CTSL were elevated after SARS-CoV-2 infection 36 , suggesting that CTSL is likely to be a potential therapeutic target for blocking viral entry 36 , 37 . CTSL has been linked to IR injury, including renal IR injury 38 and myocardial IR injury 39 . Consistent with previous studies, we also reported the crucial role of CTSL in the plasma of CPB-ARDS patients and the lung tissue of LIRI rats.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracotomy and left anterior descending coronary artery permanent ligation surgeries were performed on C57BL/6J (Envigo), Runx1- deficient, Cbfβ- deficient and respective floxed control mice using previously published standard approaches (see Extended Methods) 59, 60 .…”
Section: Methodsmentioning
confidence: 99%